The role of structured inpatient lipid protocols in optimizing non-statin lipid lowering therapy: a review and single-center experience - Gier, Chad; Gilchrist, Ian; Fordham, Matthew; Riordan, Luke; Milchan, Ella; Patel, Nidhi; Mojahedi, Azad; Choudhury, Sahana; Kits, Tara; Cohen, Regina; Doughtery, Joseph; Reilly, John P.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Dyslipidemia is a leading contributor to atherosclerotic cardiovascular disease (ASCVD). There has been a significant improvement in the treatment of dyslipidemia in the past 10 years with the development of new pharmacotherapies. The intent of this review is help enhance clinicians understanding of non-statin lipid lowering therapies in accordance with the 2022 American College of Cardiology Expert Consensus Clinical Decision Pathway on the Role of Non-statin Therapies for LDL-Cholesterol Lowering. We also present a single-center experience implementing a systematic inpatient protocol for lipid lowering therapy for secondary prevention of ASCVD.